DESIGN OF A TELEGRAM-INTEGRATED GRAFANA NETWORK MONITORING SYSTEM FOR ENHANCED FAULT DETECTION AND REAL-TIME NOTIFICATION - Hakim, Nurul Fahmi Arief; Elvyanti, Siscka; Ardiansyah, Yogi (Universitas Gunadarma, 2025)
Network device monitoring has problems such as connectivity loss between routers. Network technicians are required to monitor all network devices at all times. This article aims to discuss the results of the network device monitoring system in Building A FPTK UPI using Grafana integrated with Telegram as an effort to monitor and repair problematic network devices. The method used is simulation using network software that is adjusted to actual conditions. Grafana and Prometheus are used in creating a device monitoring system. Prometheus works to retrieve data from the SNMP (Simple Network Management Protocol) and process the data using an exporter. Grafana can create visualizations on the network device monitoring system from the data that has been processed. This study uses a simulation method on PNETLab and VMware software. Based on the results obtained, the Grafana dashboard display can display the traffic interface on the router. The dashboard displayed is when ether 2 connected to the north 2nd floor router experiences interference which causes the north 2nd floor router to not get internet network access so that a warning appears in the form of a notification message R_LT2_UTARA | Down from DSTIbot via Telegram. The repair effort for the problem was carried out by connecting ether 3 from the middle 1st floor router to the north 2nd floor router so that the north 2nd floor router still gets internet network access. The repair displays the message notification R_LT2_UTARA | Up from DSTIbot via Telegram.